Parité et disparité : sphère publique et sphère privée de la parole - Jean Le Dû; Yves Le Berre (La Bretagne Linguistique, 1996)
This paper opened the “Badume-Standard-Norme” conference which took place in Brest (June 2-4, 1994). The authors of this paper explain why they decided to organise this conference: to confront the theories they have developed while studying the Breton language and its speakers, their open-air laboratory, with the criticism of researchers interested in linguistic matters. At the forefront of these theories detailed here is “badume” (ba-dum: “at home”), used to designate the Breton language spoken locally in traditional society, and then by extension to the languages which fall within the parity register. The “standard” and the “norm”, which belong to the disparity register, are linked to it. If these instruments are used to describe the reality of Breton in Western-Brittany, what about elsewhere?